The effectiveness of natural ventilation design in low cost housing - Amin Abdullah @ Abu Bakar, Md. Hanafiah (2005)
Housing low-income families is one of the greatest problems that ail humanity. With the ever increasing awareness and concerns in building low cost houses for the low-income earners the government had set up in the 7th Malaysia Plan (1996 – 2000) a target to reach 200,000 units of low cost houses to accommodate this group. This was announced by the former Ministry of Housing and Local Government, Datuk Ting Chew Peh. Despite the steps that have been taken has it really given these people a healthy and comfortable living environment? From what has been observed most flats and low cost terraces are poorly built. This includes the materials used and also the design of the building such as openings for ventilation. Ventilation design in particular has not been taken into great consideration where problems such as window openings that do not follow the standard size requirement and rooms not having any openings at all still exist to this day. The purpose of this research was to identify the effectiveness and occupant’s satisfaction level of the design of natural ventilation for low cost terrace houses. A study will be done on single and double storey houses as well as renovated single and double. The effectiveness of these designs will be assessed from the type of occupants, the time heat is most felt and the frequency of mechanical equipment used. In order to identify the level of satisfaction among occupants, a test is conducted by using a comfy meter. From the surveys and findings being carried out, it was found that the UBBL requirements that are applied to the low cost houses are no longer viable or effective. The results achieved are only in theoretical forms and can be applied for further study in order to obtain a more accurate and suitable multi design component. The results can also be applied to other problems.